Bibliometric Analysis of Pest Management - Loso Judijanto (Westscience Press, 2026)
Pest management research has gained a considerable importance among scholars because of growing problems associated with agricultural efficiency, environmental sustainability, development of pesticide resistance, and food safety issues. In this paper, the objective is to investigate the growth, intellectual structure, collaborations, and future trends of global pest management research with the help of bibliometric analysis. The data used in the current study are obtained from scientific publications indexed in an international academic database and analyzed through VOSviewer in order to identify authorship networks, co-occurrence of keywords, citation structure, and time-related developments of the research. The results of the study show that pest management research is highly concentrated around certain topics that include pest control, pest management, biological control, insect control, pesticide application, and integrated pest management (IPM). The citation analysis proves that important studies have been involved in the process of change from traditional chemical pest management towards ecological and sustainable pest management strategies including habitat management, biopesticides, conservation of natural enemies, and biological control. The collaborations analysis proves that such countries as the USA, China, India, Australia, and several European countries are actively participating in knowledge production on the global scale but there are still opportunities for enhancing research cooperation between countries. Finally, the analysis of keyword evolution suggests that the attention of researchers focuses on sustainability, invasive species management, biotechnology, and ecological pest management techniques.